2018
DOI: 10.1037/neu0000455
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical distractibility of global and focal visuospatial attention during segmental and total compound line bisections.

Abstract: The asymmetrical global distraction during segment bisection might be related to the right hemisphere's dominance in mediating global attention and allocating attention leftward. In contrast, the asymmetrical focal distraction during full-line bisection might be related to the left hemisphere's dominance in mediating focal attention and allocating attention toward the right. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In addition, in the focal condition participants are instructed to bisect only the one segment of the compound line. In this condition, when allocating focal attention to the longer segment, healthy middle-aged participants are more distracted when the longer segment is presented on the right and the smaller segment is on the left (Mosquera et al, 2018). This result is consistent with prior studies, which have revealed that, whereas the left hemisphere mediates focal attention, the right hemisphere mediates global attention (Reuter-Lorenz et al, 1990).…”
supporting
confidence: 90%
See 4 more Smart Citations
“…In addition, in the focal condition participants are instructed to bisect only the one segment of the compound line. In this condition, when allocating focal attention to the longer segment, healthy middle-aged participants are more distracted when the longer segment is presented on the right and the smaller segment is on the left (Mosquera et al, 2018). This result is consistent with prior studies, which have revealed that, whereas the left hemisphere mediates focal attention, the right hemisphere mediates global attention (Reuter-Lorenz et al, 1990).…”
supporting
confidence: 90%
“…In contrast, in the global condition, both groups of participants were more distracted when the longer segment of this compound was on the left side. Although the exact reason for these effects is not entirely known, these results might be related to the right hemispheric dominance in mediating global attention as well as in allocating attention to the left hemispace (Heilman & Van Den Abell, 1980;Pardo et al, 1991;Mosquera et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations